Case study : PTIME Resources Company / Nur Aisyah Mohd Nadzir - Mohd Nadzir, Nur Aisyah (2020)
Technology Entrepreneurship (ENT600) is a subject that allows the student to explore the real-life business and teach us to apply technology solution for the problems arise. To complete this task, I was able to meet and interview the owner of a digital prayer hour company, PTIME Resources which is located in Kulim, Kedah. I choose this company because I find it interesting how a small company can grow into a big company and become more successful as the time goes by. It makes me curious about how the company manages to stay in the long run of business. PTIME Resources is a well-known company that manufactures digital prayer hours and it provides a different kind of designs to attract customers. These digital prayer watches are suitable to be put in mosques, personal use, and musolla or “surau”. This company has been operating for almost 3 years. The owner of this company consists of 4 people but each of them has different roles in the business. The company does not only offers the digital clock, but they also provide free installation service and after-sale service at a reasonable price. The most highlight problem of this company would be the workers. A small number of workers might be enough at the moment, but it takes more than eight workers to achieve the company mission, which is to market their product at the ASEAN level. Therefore, I have suggested Mr. Roszaimi hire more people in the company, and provide training classes for the new employees.